PROPOSAL OF A WATER QUALITY INDEX FOR THE BAIXO JACUÍ REGION, RS, BRAZIL - Teixeira, E. C.; Fachel, J. M. G.; Vecchio, G.; Migliavacca, D.; Sanchez, J. C. D.; Haase, J.; Cobalchini, S. (Geochimica Brasiliensis, 2011)